Welsh Devolution and the Union: Reform Debates after Brexit. Issue 1 (6th January 2021) - Bradbury, Jonathan
Abstract: The survey addresses three key reform debates relating to devolution in Wales. These concern first, the case for the further devolution of powers, notably those over criminal justice and policing; second, the defence of Wales' devolved powers in the context of Brexit; and third, the rooting of devolution in new constitutional ideals, primarily the Welsh government's preferred model of the UK as a voluntary association of nations, or the alternative pressed by the independence movement. In each case, there are strong pressures within Wales for resolutions which sustain and develop devolution; and in the case of independence, have the potential, with reform debates elsewhere, to transform the UK Union. However, there are also grounds for reflecting on the contested nature of further change, the long road that a case for independence may yet have to travel, and the interests of UK government.